A.04 The classification of autosomal recessive cerebellar ataxias: a consensus statement from the society for research on the cerebellum and ataxias task force. (June 2019) - Beaudin, M; Matilla-Dueñas, A; Soong, B; Pedroso, J; Barsottini, OG; Mitoma, H; Tsuji, S; Schmahmann, JD; Manto, M; Rouleau, GA; Klein, CJ; Dupre, N
Abstract : Background: There is currently no accepted classification of recessive cerebellar ataxias, a group of disorders characterized by important genetic heterogeneity and complex phenotypes. The objective of this task force was to build a consensus and develop a clinical and pathophysiological classification for recessive ataxias. Methods: The work of this task force was based on a scoping systematic review of the literature that identified recessive disorders characterized primarily by a cerebellar motor syndrome and cerebellar degeneration. The task force regrouped 12 international ataxia experts who decided on general orientation and specific issues. Results: We identified 59 disorders that are classified as primary recessive ataxias. For each of these disorders, we present geographical and ethnical specificities along with distinctive clinical and imagery features. The primary recessive ataxias were organized in a clinical and a pathophysiological classification, and we present a general clinical approach to the patient presenting with ataxia. We also identified a list of 48 complex multisystem disorders in which ataxia is a secondary feature. Conclusions: This classification is based on a scoping systematic review of the literature and results from a sconsensus among a panel of international experts. It promotes a unified understanding of recessive cerebellar disorders for clinicians and researchers.